2009
DOI: 10.3109/s10165-009-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

A significantly impaired natural killer cell activity due to a low activity on a per-cell basis in rheumatoid arthritis

Abstract: To elucidate the characterization of peripheral natural killer (NK) cells in patients with rheumatoid arthritis (RA), we investigated the NK cell activity, the expression of NK cell activating receptors and intracellular molecules. The NK activity was analyzed in 27 RA patients, 22 primary Sjögren's syndrome (SS) patients, and 15 healthy individuals using the (51)Chrominium release assay. The expression of NK cell activating receptors (NKG2D, CD244, CD2, and CD16) and intracellular molecules (granzyme B, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…We consider these findings important with regard to the negative effect of NKG2D on autoimmunity development reported previously [31,33]. Evaluating NK cytotoxicity, however, we also detected the suppression of NK effector function appearing during the disease progression, as reported by Aramaki et al in human RA [21] or Lo et al in CIA [22]. During the early arthritis phase the cytotoxicity was at the HC level, while in the late arthritis phase it showed a highly significant suppression.…”
Section: Cd11csupporting
confidence: 79%
See 1 more Smart Citation
“…We consider these findings important with regard to the negative effect of NKG2D on autoimmunity development reported previously [31,33]. Evaluating NK cytotoxicity, however, we also detected the suppression of NK effector function appearing during the disease progression, as reported by Aramaki et al in human RA [21] or Lo et al in CIA [22]. During the early arthritis phase the cytotoxicity was at the HC level, while in the late arthritis phase it showed a highly significant suppression.…”
Section: Cd11csupporting
confidence: 79%
“…Corresponding results were also presented by Dalbeth and Callan, who suggested that NK cells in the inflamed synovium interact with the macrophage/monocyte population, thus amplifying the production of inflammatory cytokines [20]. Conversely, Aramaki et al reported low, impaired NK activity in human RA [21]. Lo et al even reported that NK cells play a protective role in the development of CIA, which is mediated by interferon (IFN)-γ production suppressing the generation of Th17 cells [22].…”
Section: Introductionmentioning
confidence: 67%
“…In many instances of autoimmune disease, a reduction in number of NK cells along with decreased cytotoxic function has been observed. 43,44 In vivo studies using experimental autoimmune encephalomyelitis (EAE), which is an animal model of multiple sclerosis (MS), show increased severity and mortality when NK cells are depleted prior to disease induction. EAE animals have cellular infiltration, CNS inflammation, and demylination.…”
Section: Role In Various Disease Conditionsmentioning
confidence: 99%
“…Low perforin expressing NK cells have been reported previously in RA and systemic onset JIA. Further using functional assay reduced cytotoxicity has been seen in patients with SoJIA as well as RA [9,20,21,23,24]. A recent study on AS using degranulation assay also reported impaired NK cell cytotoxicity [24].…”
Section: Discussionmentioning
confidence: 94%